2007
DOI: 10.1111/j.1471-4159.2007.04857.x
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule profiling of tau gene expression in Alzheimer’s disease

Abstract: Tau is a microtubule-associated protein that is important for establishing and maintaining neuronal morphology. In addition to its role in normal cells, tau protein is involved in many neurodegenerative diseases, e.g. Alzheimer's disease (AD) and frontotemporal dementia, as the main component of intraneuronal aggregates. Alternative splicing of tau gene in the brain can give rise to at least six protein variants. A causative role of skewed tau exon 10 inclusion has been defined in frontotemporal dementia; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 48 publications
4
57
0
Order By: Relevance
“…More than 30 mutations have been identified among FTDP-17 patients, many of which affect tau exon 10 splicing (26,45,54,60,61,91,92,97; reviewed in references 2, 53, and 66). In addition, a number of studies have reported an altered Tau4R-to-Tau3R ratio or aberrant tau exon 10 splicing in a range of sporadic tauopathies, including progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), multiple system tauopathy with dementia (MSTD), and argyrophilic grain disease (AGD), and even in some Alzheimer's patients, among others (20,39,101; reviewed in references 2, 12, 36, and 78 and references therein). It is interesting that a significant fraction of these patients show increased levels of Tau4R without detectable mutations in the tau gene.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 mutations have been identified among FTDP-17 patients, many of which affect tau exon 10 splicing (26,45,54,60,61,91,92,97; reviewed in references 2, 53, and 66). In addition, a number of studies have reported an altered Tau4R-to-Tau3R ratio or aberrant tau exon 10 splicing in a range of sporadic tauopathies, including progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), multiple system tauopathy with dementia (MSTD), and argyrophilic grain disease (AGD), and even in some Alzheimer's patients, among others (20,39,101; reviewed in references 2, 12, 36, and 78 and references therein). It is interesting that a significant fraction of these patients show increased levels of Tau4R without detectable mutations in the tau gene.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that by using brain samples from patients with tauopathies, one cannot differentiate between cis-acting elements and trans-acting splicing factors that increase splicing in of MAPT exon 10. 30,31 From the known effect on gene expressions by the GSK3B 19 and MAPT haplotypes (see Fig 1A), we propose the following model for the epistatic interaction between the two genes as shown in Figure 3. We propose that the downstream effect of discordant GSK-3␤ and Tau levels is altered interaction with other GSK-3␤ substrates, where excess Tau is able to sequester GSK-3␤ and shunt it toward cellular pools that will have functional effects on other substrates of GSK-3␤.…”
Section: Discussionmentioning
confidence: 99%
“…In the human central nervous system (CNS), there are at least six isoforms of tau that are classified as either 3R (containing three tandem repeats) or 4R (containing four tandem repeats) (Goedert et al 1989). Conrad et al (2007) used a polymerase colony (polony)-based exon profiling platform, which allows the quantitative measure of combinatorial splicing of tau isoforms at a single molecule level. The assay uses an acrylamide gel matrix with randomly arrayed DNA templates that is processed via in-gel PCR amplification and is followed by an exon-specific oligonucleotide hybridization/single base extension.…”
Section: Regional Gene Expression Profiles In Admentioning
confidence: 99%